j DAMPAK SOSIAL EKONOMI CORPORATE SOCIAL RESPONSIBILITY (CSR) PT. INDOMARCO PRISMATAMA DISTRIBUTOR CENTER TANGERANG - Jumanah, jumanah; Islamey Assyifa , Thalitha (LPPM STIA Banten, 2025)
ABSTRACT The less than optimal CSR program carried out by PT. Indomarco DC Tangerang in terms of social and economic activities and socialization procedures that are still hampered and felt to be less comprehensive to the surrounding community. The purpose of this study was to determine the social impact and economic impact of Corporate Social Responsibility of PT. Indomarco Prismatama at the Distribution Center in Tangerang Regency. The research method used in this study is to use a descriptive research type using a qualitative approach. Corporate Social Responsibility (CSR) of PT. Indomarco Prismatama has had a real positive impact on the social and economic aspects of the community in Tangerang Regency. In the social aspect, the public facility renovation program, distribution of basic necessities, and skills training have succeeded in improving community welfare and empowering local communities. However, the scope of this program is still limited, and the lack of socialization hinders community participation. On the other hand, the economic aspect shows significant results through support for local MSMEs and absorption of local labor, which helps reduce unemployment and encourage regional economic growth. Keywords: Implementation, Corporate Social Responsibility, Social and economic.